Colon angiolipoma with intussusception resected by laparoscopy-assisted surgery: a case report. Issue 8 (10th August 2021) - Kimura, Akiharu; Morinaga, Nobuhiro; Tajima, Kohei; Ogata, Kyoichi; Kato, Hiroyuki; Sohda, Makoto; Shirabe, Ken; Saeki, Hiroshi
Abstract: Angiolipomas are benign mesenchymal tumors that often occur under the skin of the upper extremity or thoracic and abdominal walls. Angiolipomas of the digestive tract are rare. Here, we describe a case of transverse colon angiolipoma with intussusception resected by laparoscopy-assisted surgery. A 50-year-old woman visited a family hospital with complaints of left lower abdominal pain and bloody stool. Colonoscopy revealed a submucosal tumor in her left colon. She was referred to our hospital for further examination. Computed tomography revealed a low-density tumor with intussusception in the left transverse colon. Elective surgery was planned for this patient because there were no alarming symptoms such as ileus or obstruction. Laparoscopy-assisted surgery and partial resection of the left transverse colon were performed. The histopathological diagnosis was angiolipoma of the colon. Angiolipomas are benign mesenchymal tumors that rarely occur in the digestive tract. Thus, accurate preoperative diagnosis is difficult.